Urang Aring (Eclipta alba (L.) Hassk) Leaf Extract as Natural Dyes for Making Pomade - Triutari, Nurlaila; Pulukadang, Sri H. V. (Universitas Tadulako, 2023)
Dyes have an important role in the industrial sector to increase consumer interest in a product. Urang aring is a plant with color pigments that can be used as natural dyes. This study aims to utilize urang aring leaf extract as a natural hair dye for the manufacture of pomade by producing the quality of pomade preparations according to standards. The research method was carried out experimentally including determining the water content and ash content of urang aring leaves and optimizing the time of dye extraction and storage of urang aring leaf extract using a UV-Vis spectrophotometer, then making pomade based on the formulation of urang aring leaf extract and beeswax, namely: formulation I (3:3), II (5:3), and III (10:3). Pomade quality test includes: organoleptic test, homogeneity test, pH test, freeze-thaw test, and color stability test against sunlight. Based on the results of the study, it was found that urang aring leaf extract can be used as a natural dye for the manufacture of pomade with formulation III which meets the standards in the pomade quality test because it has a soft dense texture, blackish green color, and has no odor with a pH of 6 which is ideal for hair. Pomade formulation III also has a texture that does not separate at extreme temperatures and good color stability under direct sunlight for 5 hours.